Menjaga Hati dari FOMO: Living Tasawuf dan Qana’ah Santri Al-Ihya’ 2 dalam Manajemen Media Sosial - Shofa Ishmatus Sanaya; Fitriana Wijaya; Millati Asyfa Azkiya'; M Rikza Chamami (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The phenomenon of Fear of Missing Out (FOMO), which has emerged as a result of social media use, poses a mental and spiritual challenge for the younger generation, including student residents at Islamic boarding schools. The rapid flow of information and the pressure to constantly keep up with others’ activities often lead to anxiety, feelings of inadequacy, and social pressure. This study aims to explore the understanding and practice of qana’ah as a Sufi value in addressing FOMO, identify forms of living Sufism that have developed within the boarding school environment, and analyze the effectiveness of the values of qana’ah and muhasabah in supporting the mental and spiritual well-being of student boarders. This study employs a qualitative field approach using a phenomenological method conducted at the Al-Ihya’ 2 Putri Student Islamic Boarding School. Data were collected through in-depth interviews, participant observation, and documentation of student boarders who actively use social media. The results indicate that qana’ah is understood not merely as a theoretical concept but is internalized as an attitude of contentment, gratitude, and self-control in social media use. The identified practices of living tasawuf include limiting social media usage time, performing daily muhasabah, strengthening religious activities, and fostering collective awareness within the pesantren community. The values of qana’ah and muhasabah have proven effective in reducing the tendency toward FOMO, promoting inner peace, strengthening self-control, and helping students cope with social media pressures in a healthier way. This study confirms that Sufism, particularly the concept of qana’ah, is relevant as a spiritual approach to fostering balanced social media usage among the younger generation